Cover Image. Issue 6 (13th November 2021) - Escobar, Miguel; Castaman, Giancarlo; Boix, Santiago Bonanad; Callaghan, Michael; de Moerloose, Philippe; Ducore, Jonathan; Hermans, Cédric; Journeycake, Janna; Leissinger, Cindy; Luck, James; Mahlangu, Johnny; Miesbach, Wolfgang; et al.
Abstract : The cover image is based on the Original Article The safety of activated eptacog beta in the management of bleeding episodes and perioperative haemostasis in adult and paediatric haemophilia patients with inhibitors by Miguel Escobar et al., https://doi.org/10.1111/hae.14419 .